Mid-Cretaceous polar standstill of South America, motion of the Atlantic hotspots and the birth of the Andean cordillera - Somoza, Ruben (2008)
A paleomagnetic study on mid-Cretaceous rocks from the San Bernardo foldbelt (Patagonia) yields high unblocking temperature and high-coercivity magnetizations. The results indicate absence of relative vertical-axis rotations during development of the foldbelt, with the associated pole position being highly concordant with coeval poles from Brazil and Patagonia. Taken together, mid-Cretaceous poles derived from studies in widely distributed localities provide supportive evidence that South America was essentially motionless with respect to the paleomagnetic axis from ca 125 to at least 100 Ma. The paleolatitudes of South America are not consistent with the occurrence of mid-Cretaceous true polar wander, suggesting that the previously observed discrepancy between the paleomagnetic and the fixed Indo-Atlantic hotspot reference frames be related to motion of the Atlantic hotspots. In agreement with this, the discrepancy is diminished by half when the Cretaceous poles of the Americas are observed in a moving-hotpots reference frame, with the residual offset being comparable to that seen for younger time intervals. The South American paleopoles and the moving-hotspot framework provide a kinematic scenario that allows relating the extensional tectonics in the early stages of Andean evolution with episodic divergence between the trench and the continental interior. Likewise, the beginning of contractional events correlates with model-predicted westward acceleration of South America in the Late Cretaceous, suggesting that the continent episodically overrode the Andean trench by those times. We argue that this change in Andean tectonic regime is associated to major plate reorganization at ca 95 Ma. © 2008 Elsevier B.V. All rights reserved.